A divided branch: Legislative chambers and the varied effects of party strength on policy outcomes in the American states. (5th January 2015) - Thom, Michael
State legislatures have received considerable attention as drivers of policy outcomes, but research designs typically paint this branch of government with broad strokes. Studies that investigate the influence of party control or party strength on public policy often fail to conceptualize the upper and lower legislative chambers as unique bodies. But policy enactments at the state level depend on two chambers that are not carbon copies of one another. Using pension funding, health care and immigration reform as illustrations, this study demonstrates that altering models to include party measurements for both chambers can lead to substantively different conclusions about the effect of partisanship on policy outcomes. Further differences arise when binary measures of majority control are used instead of continuous measures of party strength. If accurate inferences are to be drawn from empirical models, these findings suggest scholars must conceptualize legislative measurement with due care.